Aplikasi Teknik Polymerase Chain Reaction (PCR) Menggunakan Primer Degenerate dan Spesifik Gen AV1 Untuk Mendeteksi Begomovirus Pada Tomat (Lycopersicon esculentum Mill.) - Tri J. Santoso; Sri H. Hidayat; M. Herman; , Sudarsono (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTBegomoviruses infection has been reported and found in several important vegetable crops included tomato. Nevertheless, the information of detection and identification of Begomovirus infecting tomato plants in some of tomato production areas using PCR technique has not been widely reported. The objective of this research was to detect Begomovirus infecting tomatoes in some of tomato production areas of East Java, Central Java, Special Province of Jogjakarta and West Java using PCR technique with degenerate and specific primers. PCR amplification of Begomovirus genome was conducted by using a pair of degenerate primers, i.e. PAL1v1978-F and PAR1c715-R and specific primer, AV1-F/R. For confirmation the virus, it was conducted a virus transmission from the symptomed plant tomato sampel to healthy plants by using whiteflies vector. The results of this research showed that the symptomed plants collected from several tomato production areas of East Java, Central Java, Special Province of Jogjakarta and West Java indicated that those plants have been infected by Begomovirus following PCR detection using a pair of degenerate primers. The Begomovirus infection was indicated by the PCR amplified product with the size of 1500 bp. The results of PCR amplification using specific primers AV1-F/R to detect the genus of Begomovirus showed that all samples of plant collections generated of 780 bp DNA fragment. Confirmation of the virus through transmission by whitefiles vectors in greenhouse from the symptomed plants and the positive PCR samples showed that the virus transmission process was succesfully conducted with indication of the emergence of symptoms in healthy plants.Keywords: tomato ( Lycopersicon esculentum Mill.) , Begomovirus, PCR technique, degenerate primerABSTRAKHasil penelitian sebelumnya menunjukkan bahwa Infeksi virus begomovirus di beberapa tanaman sayuran termasuk tanaman tomat. Namun demikian, penelitian yang memberikan informasi mengenai deteksi dan infeksi dari virus begomovirus yang menginfeksi tanaman tomat dengan menggunakan teknik PCR masih perlu diteliti lebih lanjut. Tujuan dari penelitian adalah untuk mendeteksi begomovirus yang menginfeksi tanaman tomat di beberapa daerah produksi tomat dari Jawa Timur, Jawa Tengah, Yogyakarta, dan Jawa Barat menggunakan teknik PCR dengan primer degenerate dan spesifik. Amplifikasi PCR genom begomovirus dilakukan dengan menggunakan sepasang degenerate primer yaitu PAL1v1978-F dan PAR1c715-R, serta primer spesifik adalah AV1-F/R. Konfirmasi virus dilakukan dengan teknik penularan virus oleh vektor kutu kebul ke tanaman sehat. Hasil penelitian menunjukkan bahwa sampel-sampel tanaman tomat bergejala yang dikoleksi dari beberapa daerah di Jawa Timur, Jawa Tengah, Jawa Barat dan D. I . Jogjakarta mengindikasikan adanya infeksi oleh Begomovirus setelah dideteksi menggunakan teknik PCR dengan primer degenerate. Hasil amplifikasi PCR menggunakan primer spesifik AV1-F/R untuk mendeteksi genus Begomovirus menunjukkan bahwa semua sampel tanaman koleksi menghasilkan amplikon yang berukuran 780 bp. Konfirmasi virus melalui penularan dengan vektor kutu kebul di rumah kaca dari sampel tanaman sakit dan positif PCR menunjukkan terjadinya proses penularan virus yang ditandaidengan munculnya gejala-gejala pada tanaman yang sehat.Kata kunci: Begomovirus, Lycopersicon esculentum, Primer degenerate, Tehnik PCR.